Theory and explanation in geography - Yeung, Henry Wai-Chung (London John Wiley & Sons Ltd., 2024)
Theory and Explanation in Geography Yeung presents us with a rare thing - an argument for geographical theory with forms of causal explanation at its heart. The book is both modest and ambitious. Modest in its insistence on mid-level theory without a call for some new "turn" or advocacy for any particular approach. Ambitious in its insistence that existing theoretical traditions are inadequate or incomplete insofar as they lack causal explanatory power. Geographers will be inspired and/or infuriated by Yeung's arguments in this provocative and cogently argued call to theoretical arms for many years to come.